Macro-social marketing as a government’s opportunity to make a positive influence on societal behaviour - Volgasts, Emils; Sloka, Biruta (University of Latvia, 2020)
Governments work hard to make their district a better place to live, sometimes when society does not recognize what has been done and it indicates the real issue – information asymmetry. To improve information flow between government and society as well as active social change it is possible to use macro-social marketing. In a few cases, it is already happening but there are many more where it could be used by the government. Problem statement – there is information asymmetry between government and society, that reflects on the social development of the country on a macro-level. Aim – to investigate macro-social marketing and its ability to improve the communication flow between government and society while making a positive impact on society. Main research methods used – scientific publications and previous conducted research analysis, for empirical part a quantitative non-parametric method for statistical. The authors study macro-social marketing and its implementation of good practice, CSDD, in Latvia. First, it is important to get a common understanding of what macro-social marketing is and how it differs from micro social or social marketing. Second, macro-social marketing is already in use but not always governments are aware that they are using it, so authors will stimulate awareness by mentioning successful cases where macro-social marketing has been used in addition by doing one in-depth case study of a Latvian government organization called CSDD that is responsible for road traffic security in Latvia. In the end, there will be available main conclusions, proposals, and recommendations for the Latvian government that can be used to positively influence society as well as other stakeholders. Main results and findings of the paper – the article provides new information about macro-social marketing and its ability to make a positive impact on society if used right by the Latvian government and public institutions. Analyze macro-social marketing Latvia CSDD case; make conclusions about macro-social marketing and assemble recommendations for Latvian government. Overall, the article answers do macro-social marketing is a way for the government to make a positive influence on society.
Keywords: macro-social marketing; social marketing; society; government; public sector; Research Subject Categories::SOCIAL SCIENCES::Business and economics